2019
DOI: 10.1002/dac.4060
|View full text |Cite
|
Sign up to set email alerts
|

Advanced IEEE 802.11ax TCP aware scheduling under unreliable channels

Abstract: In this paper, we suggest advanced IEEE 802.11ax (WiFi) TCP-aware scheduling strategies for optimizing the TCP Goodput AP operation under transmission of unidirectional TCP traffic to downloading stations. Our scheduling strategies optimize the TCP Goodput performance using the capability for Multi User transmissions over the Uplink, first introduced in IEEE 802.11ax, together with Multi User transmissions over the Downlink. The scheduling strategies are based on Transmission Opportunities (TXOP), and we sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Some work addressed improving scheduling in the uplink by minimizing delay (Bankov et al, 2017;Bankov et al, 2018) and improving scheduling strategies for TCP traffic (Sharon & Alpert, 2019). While in (Naik et al, 2018) the performance analysis of uplink multiuser OFDMA and in (Sharon & Alpert, 2017) the scheduling strategies and throughput optimization were explained.…”
Section: 11ax Scheduling Basedmentioning
confidence: 99%
“…Some work addressed improving scheduling in the uplink by minimizing delay (Bankov et al, 2017;Bankov et al, 2018) and improving scheduling strategies for TCP traffic (Sharon & Alpert, 2019). While in (Naik et al, 2018) the performance analysis of uplink multiuser OFDMA and in (Sharon & Alpert, 2017) the scheduling strategies and throughput optimization were explained.…”
Section: 11ax Scheduling Basedmentioning
confidence: 99%
“…The authors in [12] perform analysis for different node densities and traffic types in HEW network. In [13], the authors suggest a TCP-aware scheduling strategy for optimizing the transmission of TCP traffic. The number of stations and resource allocation algorithms are the only deployment options evaluated in [14,15], respectively, to measure the corresponding effects.…”
Section: Related Workmentioning
confidence: 99%
“…They conducted evaluations of MIMO and OFDMA transmissions in IEEE 802.11ax against the carrier-sense multiple access with collision avoidance (CSMA/CA) MAC of IEEE 802.11ac with the SU and MU modes for various numbers of STAs scenarios in both reliable and unreliable channel environments. The authors of [ 18 ] suggested advanced IEEE 802.11ax TCP-aware scheduling strategies to optimize the performance using MU UL and MU DL transmissions. They were based on transmission opportunities (TXOP) and can control achieved goodput versus delays.…”
Section: Related Workmentioning
confidence: 99%